English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-28 14:29:55 · 4 answers · asked by lindasalicea 1 in Science & Mathematics Mathematics

4 answers

(m^4)^3(m^2)^9/(m^3)^2
= (m^12)(m^18)/(m^6)
= m^(12+18-6)
= m^24

2007-06-28 14:32:50 · answer #1 · answered by Kemmy 6 · 1 0

(m^4)^3 =m^4.3 =m^ 12

(m^2)^9 =m^2.9= m^18

m^3)^2 = m^3.2 =m^6

= (m^12)(m^18)/m^6

=m^12 + 18/m^6

=m^30/m^6
using law of indicies m^a/m^b = m^a-b
=m^30 - 6

=m^ 24

2007-07-02 14:20:49 · answer #2 · answered by ravi s 1 · 0 0

= m^(12).m^(18) / m^(6)
= m^(30) / m^(6)
= m^(24)

2007-07-02 08:15:15 · answer #3 · answered by Como 7 · 0 0

m^12(m^18)/m^6
m^30/m^6
m^24

2007-06-28 14:32:51 · answer #4 · answered by Anonymous · 0 1

fedest.com, questions and answers